Rotating Machinery and Signal Processing : Proceedings of the First Workshop on Signal Processing Applied to Rotating Machinery Diagnostics, SIGPROMD '2017, April 09-11, 2017, Setif, Algeria /: Proceedings of the First Workshop on Signal Processing Applied to Rotating Machinery Diagnostics, SIGPROMD '2017, April 09-11, 2017, Setif, Algeria. ([2019]) - Unknown
No abstract available